Prevalence of Atopobium vaginae and Porphyromonas somerae in the Genital Tract of Women Undergoing Hysterectomy for Benign and Malignant Disease at a South Indian Tertiary Hospital - Vinodhini Kadirvel; D. Jayalakshmi; Rakesh Singh; P. Veena (Journal of Mid-Life Health)
Background: Endometrial cancer is the third most common cancer affecting the lower genital tract of women. Studies have shown modifiable and nonmodifiable risk factors for the same, which include genetic factors and microbes. Alteration in the microflora of the lower genital tract might be a triggering factor for many pathological and malignant conditions. Hence, we tried to explore the occurrence of Atopobium vaginae and Porphyromonas somerae in the lower genital tract of women with endometrial cancer and the factors associated with them. Materials and Methods: The study enrolled 64 patients aged between 40 and 80 years, of which 32 cases were cases of endometrial cancer and 32 cases had benign gynecological diseases. After taking the history and demographic profile of the patients, three swabs from the cervix and vagina were sent for gram staining, culture with blood and MacConkey agar, and antibiotic susceptibility tests. A real-time polymerase chain reaction was also done for molecular identification of organisms. Results: Around 50% of women with endometrial cancer had isolated colonization with A. vaginae and P. somerae, with 25% showing the coexistence of both the organisms, whereas the benign gynecological disease group displayed absence of any organisms in 56% of women. Conclusion: Coexistence of A. vaginae and P. somerae in the lower genital tract showed a significantly higher occurrence of endometrial cancer in comparison to those having either only one.